Cosmic collisions / [ (Chatsworth, CA : Image Entertainment, 2010)
Content: Collision: earth They have left deep scars and are responsible for one of the biggest extinctions in history. Learn everything there is to know about meteor clashes with earth and how scientists are preparing for the next assault. Collision: Solar System Travel through our cosmic neighborhood as we examine how collision created our moon, left gashes on Jupiter and how pieces of Mars ended up in our backyard Galactic Collision Galaxies smash into each other with the force of nuclear bombs. Journey through space and discover the cosmic battles being waged between celestial bodies